Assessment of power quality in a microgrid with power electronic converters - Ivry, Preye Milton; Thomas, David W.P.; Sumner, M. (2016)
This paper highlights the importance of assessing Power Quality (PQ) of microgrids using the recommended indices as stated in IEEE 519 and IEEE 1547 standards. It assesses the microgrid PQ by verifying if converter harmonics at the Point of Common Coupling (PCC) to the grid complies or exceeds the IEEE 519 standard on harmonic limit.